2021
DOI: 10.1080/19336918.2021.1911472
|View full text |Cite
|
Sign up to set email alerts
|

MAGI1 localizes to mature focal adhesion and modulates endothelial cell adhesion, migration and angiogenesis

Abstract: MAGI1 is an intracellular adaptor protein that stabilizes cell junctions and regulates epithelial and endothelial integrity. Here, we report that that in endothelial cells MAGI1 colocalizes with paxillin, β3-integrin, talin 1, tensin 3 and α-4-actinin at mature focal adhesions and actin stress fibers, and regulates their dynamics. Downregulation of MAGI1 reduces focal adhesion formation and maturation, cell spreading, actin stress fiber formation and RhoA/Rac1 activation. MAGI1 silencing increases phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Recently, MAGI1 was found present in mature focal adhesions in HUVEC cells in colo-calization with the known focal adhesion-associated molecules paxillin, α-actinin and β3-integrin. Experimental downregulation of MAGI1 in HUVEC reduced focal adhesion formation and maturation, cell spreading, actin stress fiber formation, and RhoA/Rac activation [76]. This is consistent with MAGI1 contributing to regulate focal adhesion maturation.…”
Section: Magi1 Vascular Functionssupporting
confidence: 76%
See 2 more Smart Citations
“…Recently, MAGI1 was found present in mature focal adhesions in HUVEC cells in colo-calization with the known focal adhesion-associated molecules paxillin, α-actinin and β3-integrin. Experimental downregulation of MAGI1 in HUVEC reduced focal adhesion formation and maturation, cell spreading, actin stress fiber formation, and RhoA/Rac activation [76]. This is consistent with MAGI1 contributing to regulate focal adhesion maturation.…”
Section: Magi1 Vascular Functionssupporting
confidence: 76%
“…Likewise, MAGI1 was shown to bind to PRKX, a protein kinase that modulates angiogenesis, however, if MAGI1 regulates PRKX functions through this interaction needs further evaluation [75]. A recent study showed that MAGI1 downregulation in ECs promotes pseudocapillary and endothelial network formation, while MAGI1 overexpression reduces endothelial cell tubulogenesis in vitro and angiogenesis in vivo in a transgenic mouse model [76].…”
Section: Magi1 Vascular Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjacent to the plasma membrane, paxillin, focal adhesion kinase (FAK), cellular sarcoma (c-Src, herein Src), kindlin 1 and the talin head domain (N-terminus) co-localise with integrin cytoplasmic tails inside the integrin signalling layer. Talin (C-terminus) and vinculin build the intermediate force transduction layer, whereas actin binding proteins (>50 nm beneath the plasma membrane), including vinculin, zyxin, α-actinin and vasodilatator-stimulated phosphoprotein, in conjunction with actin, form the actin regulatory layer ( Refs 101,[148][149][150][151][152].…”
Section: Integrins and Their Role In Cartilage Mechanotransductionmentioning
confidence: 99%
“…In endothelial cells, MAGI1 promotes focal adhesion maturation and reduces its turnover. This process involves increased endothelial cells adhesion to the extracellular matrix, via the transient increase in both RhoA and Rac1 activities, and reduces invasiveness and tubulogenesis in vitro, and suppresses angiogenesis in vivo [ 196 ].…”
Section: Implication Of Magi Molecular Scaffolds In the Control Of Carcinogenesismentioning
confidence: 99%